Analysis and Recommendations of the Problems Encountered in Electronic Record Management Practices : The Example of Ministry of Development - Umut, Gülçin; Külcü, Özgür (Information World, 2014)
Records management has changed by e-government applications within the framework of information technology. In this regard, it is required to analyse national and international conditions to determine the problems and expectations to develope suitable systems for organizational and administrational needs. Within this scope, the context of the study is the electronic records management practices in the Ministry of Development Central Organization. Questionnaire was sent to 804 clients at Central Organization in Ankara who have power to use electronic records management systems and turnout at the questionnaire was determined as 167. With the performed analysis, the systems EBYS, AVBYS and KBTarama sistemi which are in the context of the electronic records management practices in Ministry of Development, were evaluated. As a conclusion the systems have been revelaled, the problems are determined and recommendations are given on the subject.
Keywords: Records management; Organizational records management; Electronic records management; Electronic records management systems; Ministry of Development